Environment-friendly anti-seepage grouting material with controllable particle size and detectable grouting effect and construction process thereof
By developing a new green and environmentally friendly grouting material in civil engineering, the chemical reaction of organic matter and metal ions is used to generate flocs of controllable sizes, the leakage problem of traditional grouting materials in treating underground engineering and water conservancy engineering is solved. , realizes efficient pore sealing and permeability control, and improves the safety and stability of the project.
Patent Information
- Application Number
- CN202411640695.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
AI Technical Summary
When traditional grouting materials deal with leakage problems in underground engineering and water conservancy projects, they have problems such as high viscosity, poor fluidity, inability to effectively penetrate small pores and may cause structural instability.
A new green and environmentally friendly grouting material is developed to generate flocs of controllable sizes through the chemical reaction of organic matter and metal ions, and to inject them into the pores of soil by permeation grouting to achieve pore sealing and permeability control.
This material has good injectability and environmental friendliness, and can effectively diffuse to the fine pores of the soil, forming a reliable impermeability barrier, reducing the permeability of the soil, and improving the safety and stability of the project.
Smart Images

Figure CN119490850A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering anti-seepage, and specifically relates to an environmentally friendly seepage-reducing grouting material with controllable particle size and detectable grouting effect and a construction process thereof. Background Art
[0002] Water conservancy infrastructure is related to national security, economic lifeline and people's well-being, and plays an important role in national strategy. Among them, reservoirs are common and important agricultural water conservancy facilities. When reservoirs are close to or reach their designed service life, it is necessary to remove hazards and reinforce dangerous reservoirs. At the same time, with the rapid development of municipal projects such as underground rail transit and integrated pipelines, underground engineering leakage has become the main geological disaster faced in underground space development. Therefore, anti-seepage is crucial in water conservancy projects, underground projects and pollutant migration control.
[0003] In nature, soil often undergoes ashification, such as Figure 1 As shown. Podzolization refers to the erosion of minerals in the surface soil under strongly acidic conditions, and its iron and aluminum components are leached into the lower soil and deposited in the subsoil. During the soil formation process, almost impermeable B layer sediments can often be found. Researchers generally believe that the formation of the impermeable layer is because the organic matter in the topsoil layer A and the soluble multivalent metals (such as iron and aluminum) in the leached layer E form precipitates through complex reactions, and then migrate to deeper soil layers, resulting in a decrease in the permeability coefficient, even to the point of being almost impermeable. For hundreds of years, these precipitates have shown good stability in the soil.
[0004] In response to leakage problems in engineering projects, traditional grouting materials (such as ordinary cement, cement-water glass, cement-clay and polymer grouting materials, etc.) have many limitations. For example, although chemical treatment methods for cementitious materials such as cement and polymers are widely used, these materials usually have high viscosity and low fluidity, which limits their ability to be injected into pores or cracks, especially pores with a diameter or width of less than 0.2 mm. In addition, the particle size of traditional anti-seepage materials is often larger than the size of formation cracks, resulting in the inability to achieve effective penetration grouting, and only splitting grouting can be used. This will not only destroy the integrity of the original structure, but also cause high pore water pressure due to the short grouting distance, increasing the risk of instability of the original structure.
[0005] In recent years, organic polymer grouting materials such as polyurethane have received extensive attention as new grouting materials. They are used in dams, dikes, tunnels and underground projects due to their good permeability, impermeability and high strength. However, the toxicity and anti-aging properties of polyurethane materials still need to be improved, and their mechanical properties are greatly affected by storage time, temperature and humidity, and will decline over time. In addition, microbial geotechnical technology (such as microbial induced carbonate deposition technology) is also developing rapidly. Although this technology has the advantages of low viscosity and diversified applications, it has high requirements for the culture environment of microorganisms. At present, there is no perfect construction method, which limits its application in geotechnical engineering.
[0006] In summary, if we can utilize the ashing effect in nature to develop a new type of green and environmentally friendly grouting material, it will definitely have important application prospects. Summary of the invention
[0007] In order to overcome the shortcomings of the above-mentioned prior art, based on the podzolization in nature, the present invention proposes a new type of green environmentally friendly grouting material, which is particularly suitable for the seepage reduction treatment of sites such as dams, levees, and landfills. During the podzolization process, organic acids and metal cations (such as aluminum and iron) form an impermeable deposition layer in the deep soil layer through complexation reaction and migration. This process reveals the complex interaction mechanism between organic matter and metal oxides, and the generated flocculent structure can significantly reduce the permeability of the soil.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a seepage-reducing grouting material, which comprises metal ions and soluble organic matter.
[0010] Preferably, the metal ions include Al 3+ or Fe 3+ , provided by the corresponding metal salts.
[0011] Preferably, the soluble organic matter includes water-soluble potassium humate or water-soluble sodium humate.
[0012] The second aspect of the present invention provides a seepage-reducing grouting construction process, which specifically comprises: using the seepage-reducing grouting material described in the first aspect as the grouting raw material, dissolving metal ions and soluble organic matter in degassed and demineralized water respectively, mixing the two solutions to generate flocs, and then injecting them into the pores of the soil through infiltration grouting, thereby achieving effective pore plugging and permeability control.
[0013] Preferably, the grouting speed is 1.1×10 -6 m 3 ·s -1-5.5×10 -7 m 3 ·s -1 .
[0014] Preferably, after mixing the two solutions, the pH of the mixed solution is 4-8.
[0015] Preferably, after the flocs are generated, the size of the flocs is 17 μm-1000 μm.
[0016] The present invention has developed a green grouting material with controllable size, which generates flocculent precipitates through chemical reactions between organic matter and metal ions, and can inject the generated floccules into soil pores through infiltration grouting, thereby achieving effective pore plugging and permeability control. In the grouting process of the present invention, the size of the floccules decreases with the increase of stirring speed, and the size of the floccules increases with the decrease of pH value at the same stirring rate. Therefore, the size of the injected metal-organic floccules can be controlled by adjusting the reaction conditions (such as stirring rate or pH value), thereby ensuring injectability and ensuring its adaptability under different soil pore conditions. The method of the present invention not only imitates the ashing process in nature, but also provides flexible size control capabilities, and is suitable for precise infiltration reduction treatment under different engineering requirements. The present invention has the following advantages:
[0017] Preferably, the molar mass ratio (M / C) of metal ions to soluble organic matter is greater than 0.06.
[0018] Preferably, during the grouting process, the resistance method is used to detect the injection effect of the metal-organic floccules. The grouting construction process of the present invention can realize the application of real-time non-destructive testing technology. In view of the problem that the grouting quality is difficult to detect in the traditional grouting process, the resistivity method is used to carry out real-time non-destructive testing during the grouting process, ensuring that the grouting quality can be monitored and evaluated in a timely manner.
[0019] Preferably, the device used for grouting includes but is not limited to the one-dimensional grouting device shown in Chinese invention patent CN208653993U.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] To address leakage problems in engineering projects, traditional methods mostly use physical means (such as sheet pile barriers or geomembranes). At the same time, with the application of cementitious materials such as cement and polymers, chemical treatment methods are also widely used in geotechnical engineering. However, this type of injection material often has high viscosity and poor fluidity, resulting in a limited diffusion range of the grouting barrier, and is prone to high pore water pressure during construction, which may cause the risk of instability of the original structure. In the past decade, microbial geotechnical technology has also made rapid progress, but the field application of technologies such as microbial induced carbonate deposition (MICP) is still limited, mainly because it has strict requirements on the culture environment of microorganisms and lacks mature construction technology.
[0022] To this end, the present invention proposes a new type of green seepage reduction grouting material, which uses metal ions and organic matter widely present in nature as raw materials, reacts to generate floccules, and effectively reduces the permeability of the soil through a series of physical and chemical processes. Compared with traditional cementitious materials, the raw materials of the slurry are all components widely present in nature, have good injectability and environmental friendliness, and the generation of floccules has low environmental requirements and controllable size characteristics. For example, when the stirring rate is 150 rpm, 300 rpm, and 450 rpm, the grading curve shifts to the left, and the corresponding maximum particle sizes are 1956, 832, and 335 μm, respectively, and the floc sizes corresponding to the maximum peak values are 708.76, 218.74, and 106.32 μm. It shows that with the increase of rotation speed, Al-OM floccules particles are broken and the particle size becomes smaller. At the same time, after injecting the same slurry, with the increase of injection rate, the injection length of Al-OM flocs in the sand column increases. Therefore, by controlling the different stirring rates and the size of the flocs, a wider range of grouting diffusion can be achieved, effectively forming a seepage-reducing barrier. This feature significantly improves the injectability of the grouting material, allowing it to penetrate smoothly into the fine pores of the soil during construction, avoiding excessive pore water pressure. In addition, through precise size control, the grouting material can adjust the diffusion radius according to specific engineering needs to reduce the risk of disturbance to surrounding structures. The application of this green and environmentally friendly grouting material not only overcomes the defect of poor fluidity of traditional cementitious materials, but also provides a more flexible engineering solution that can adapt to complex construction conditions and effectively solve the leakage problem of the soil.
[0023] Specifically, the new green seepage-reducing grouting material provided by the present invention has the following advantages:
[0024] (1) Economic and environmentally friendly: This grouting material is low-cost and abundant in source, which reduces the negative impact on the environment. (2) High efficiency: By adjusting the stirring speed, the size of the generated flocs can be effectively controlled, so that precise grouting can be achieved at the geotechnical engineering site, significantly improving the injectability of the slurry. (3) Superior permeability control: This slurry can effectively diffuse to a certain range, forming a reliable barrier, effectively solving the problem of soil permeability, and improving the safety and stability of the project. (4) Easy to operate: The slurry preparation process is simple, the operation is easy to master, suitable for rapid on-site construction, and improves the construction efficiency of the project. (5) Strong adaptability: The physical and chemical properties of this grouting material do not have high environmental requirements, have wide application potential, and are suitable for grouting needs under different geological conditions.
[0025] Through the above-mentioned innovative advantages, the present invention provides a safer, more economical and more environmentally friendly grouting solution for geotechnical engineering, significantly improving the deficiencies of traditional grouting materials in leakage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the effect of pH value on floc size;
[0027] Figure 2 is the size distribution of AL-OM at different rotation speeds;
[0028] Figure 3 The photos are of one-dimensional grouting test using the test device of Chinese invention patent CN208653993U;
[0029] Figure 4 The distribution photos of slurry in the soil column after the injection test and the corresponding resistivity distribution map are shown. The actual photo on the left shows the physical distribution of the slurry after injection, and the resistivity maps in the middle and right show the distribution of resistivity inside the soil column through color changes.
[0030] Figure 5 To investigate the effect of injection velocity on the reduction of permeability coefficient when conducting a one-dimensional grouting test using the test device of Chinese invention patent CN208653993U;
[0031] Figure 6 is the distribution length in the sand column at different initial injection rates;
[0032] Figure 7 Schematic diagram of the principle of reducing permeability coefficient by metal-organic flocs. DETAILED DESCRIPTION
[0033] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0035] The present invention provides a new type of green seepage reduction grouting material, which uses metal ions and organic matter widely existing in nature as raw materials, reacts to generate flocs, and then injects the generated flocs into the pores of the soil through infiltration grouting, thereby effectively reducing the permeability of the soil. The working principle of the present invention is as follows:
[0036] (1) Chemical properties of organic matter:
[0037] The ion binding properties of organic matter are mainly determined by its functional groups, of which carboxyl and phenolic groups are key binding sites (the structural formula below shows the important functional groups of organic matter). These functional groups undergo protonation and deprotonation reactions when interacting with other chemicals, which is the basic process of proton (H+) transfer between different chemical species. Carboxyl groups account for about 69%-82% of the total acidity of humic acid, and the remaining acidity mainly comes from phenolic groups.
[0038]
[0039] When carboxyl and phenol groups are deprotonated, free electron pairs are released, which can coordinate with metal cations to form a stable electron layer structure. This phenomenon is called site-specific ion binding. In addition to this specific binding, the deprotonation of functional groups also makes the organic molecules carry a net negative charge, which further interacts with metal cations in the solution through electrostatic effects. This binding mechanism enables organic matter to have efficient ion binding ability in complex chemical environments.
[0040] The deprotonation process of the functional group is shown in Equation 1, which makes the surface of the organic molecule negatively charged. Due to the high abundance and strong acidity of the carboxyl group, it is the main contributor to the net negative charge on the surface of the organic molecule, and its acidity is stronger than that of the phenol group. On the other hand, the phenol group is the main site for binding with metal ions, especially aluminum ions (Al 3+ ), iron ions (Fe 3+ ) and copper ions (Cu 2+) and other metal ions have higher binding affinity, which is significantly better than the carboxyl group. Normally, the carboxyl group is deprotonated at a pH value higher than 4.4, while the deprotonation of the phenol group requires a pH value higher than 9.5. This difference indicates that the carboxyl group is more likely to provide negative charges under lower pH conditions, while the phenol group is more suitable for binding with metal ions under higher pH conditions.
[0041]
[0042] (2) Dissolution of metal ions:
[0043] The hydrolysis process of metal cations is a chemical reaction of the interaction between metal ions and water molecules, which is mainly manifested in that metal cations combine with water molecules in water and make the solution acidic by releasing hydrogen ions (H+).
[0044] The hydrolysis reaction is shown in Equation 2:
[0045]
[0046] in:
[0047] ·M z+ For metal cations.
[0048] n is the number of water molecules, usually 4 to 6.
[0049] ·[M(H2O) n ] z+ It is a hydrated metal ion.
[0050] For example: The hydrolysis of aluminum ions is:
[0051] When metals such as aluminum are added to water, hydrolysis occurs to form metal hydroxide ions. The solubility of aluminum in water is closely related to the pH value of the environment, because the ability of aluminum to form complexes with organic matter is affected by its chemical state and, therefore, by the pH value. Equation 3 describes the solubility of aluminum ions Al 3+ The gradual hydrolysis process in water, that is, through the reaction with water molecules, gradually forms various aluminum hydroxide species. Each equation represents a deprotonation (removal of a proton H + ) equilibrium reaction, and the corresponding equilibrium constant K1 is given. K1 is used to describe the equilibrium concentration relationship between different aluminum species under specific conditions. When K1 = 4.95, aluminum ion Al 3+ Reacts with water molecules to form Al(OH) 2+ (an aluminum ion with a hydroxyl group) and a proton H + ; When K2=5.6, Al(OH) 2+ Further hydrolysis to form Al(OH)2+ and another proton H + When K3=6.7, the aluminum species with two hydroxyl groups is Al(OH) 2+ Further hydrolysis forms a neutral molecule Al(OH)3 (aluminum hydroxide) and a proton. When K4=5.6, in this reaction, the neutral aluminum hydroxide Al(OH)3 continues to deprotonate to form Al(OH) 4- (aluminum ion with four hydroxyl groups) and a proton. When K5 = 31.5, aluminum hydroxide Al(OH)3 completely dissociates into aluminum ions Al 3+ and three hydroxyl ions OH - .
[0052]
[0053] It can be seen that under acidic conditions (low pH), Al 3+ ions dominate, while under alkaline conditions, Al(OH)4 - ions are dominant. 3+ Aluminum in the form of aluminum has the highest positive charge and can provide the most binding sites to form complexes with organic matter. On the other hand, pH value also affects the main binding sites of organic matter. Therefore, the effective binding between aluminum and organic matter can be promoted by adjusting the pH range, thereby improving its application effect in water treatment and soil improvement.
[0054] (3) Complexation of organic matter and metals:
[0055] The interaction between organic compounds and metals (such as aluminum and iron), including coagulation and flocculation, strongly depends on the chemical properties of both parties. Coagulation is the process of destabilizing suspended colloids or particles, resulting in the formation of aggregates of small particles. In the subsequent flocculation process, these destabilized and aggregated particles further combine to form larger aggregates. Among them, the present invention confirms that aluminum (Al) and iron (Fe) can form stable complexes with organic matter (OM), and the present invention only uses aluminum as an example to explain.
[0056] Due to its high valence, aluminum is able to combine with multiple organic molecules simultaneously to form aluminum-organic flocs. Such flocs are cloud-like aggregates formed by continuous collisions between particles. Depending on the characteristics of the organic matter and environmental conditions, the size of flocs found in aquatic systems can range from a few microns to 1000 microns. When the metal to carbon ratio (M / C ratio) exceeds 0.06, the soluble aluminum-organic complex will precipitate rapidly, and the reaction is shown in Equation 4:
[0057] Aa (aq) +bOM (aq) →cAl-OM (s) (4);
[0058] Where a, b and c are the stoichiometric coefficients.
[0059] Therefore, the method of the present invention not only imitates the ashing process in nature, but also provides flexible size control capabilities, and is suitable for precise infiltration reduction treatment under different engineering requirements.
[0060] The green seepage reduction grouting material of the present invention and its use effect are described in detail below by way of Examples 1 and 2: Example 1: A green seepage reduction grouting material and characterization of its characteristics
[0061] (1) Preparation of grouting materials
[0062] 1) Select soluble organic matter: Soluble organic matter can be selected from organic matter that can pass through a 0.45 μm sieve. Purified and chemically modified 100% water-soluble potassium humate (sodium) can be selected, such as 100% water-soluble potassium humate HUMIN-P775 produced by the German biotechnology company biotech, whose main elements are nitrogen (1.025%), carbon (42.175%), hydrogen (3.475%) and sulfur (0.8545%).
[0063] 2) Select metal source: Al plays an important role in the ashing process in nature 3+ and Fe 3+ Both can be used as metal sources. 3+ The coordination bond between them is stronger, but the Al-OM complex is less affected by the redox reaction of the surrounding environment and is more stable. Different metal sources can be selected according to needs. In this embodiment, aluminum is taken as an example, and AlCl3·6H2O white crystalline powder is selected as the experimental metal source to provide Al 3+ .
[0064] 3) Generate organic-metal floc precipitate as slurry: Dissolve metal source powder AlCl3·6H2O and soluble organic powder water-soluble potassium humate in degassed and demineralized water at specified concentrations (for example, AlCl3·6H2O solution concentration is 48.3 g / L, organic powder concentration is 5 g / L), mix them in proportion and react to generate floc precipitate (Al-OM). For example: Set the molar mass ratio M / C of aluminum Al to carbon C to 0.1. First, calculate the molar number of carbon based on the carbon content in the OM solution, assuming that the mass of carbon in the OM solution is C OM grams, the molar mass of carbon is 12 g / mol, so the number of moles of carbon is: n C =C OM / 12; According to the set M / C ratio of 0.1, the molar number of Al n A l is 0.1 times the molar number of carbon, that is: n Al=0.1×n C ; The molecular weight of AlCl3·6H2O is known to be 241.43 g / mol, so the mass of AlCl3·6H2O required is n A l×241.43.
[0065] (2) The size of the generated flocs depends on the pH value of the reaction solution.
[0066] The particle size distribution of the Al-OM floccules of this example was tested by Mastersizer 2000 laser particle size analyzer at the same stirring rate (300 rpm) and different pH values. The results are as follows: Figure 1 As shown. At pH = 8, the particle size is mainly concentrated in the smaller particle size range, and most of the particles are between 3 and 200 microns. The peak of the volume distribution is located in the lower particle size region. At pH = 6, the particle size becomes slightly larger, mainly distributed in the range of 80 to 600 microns, and the volume peak shifts to the right relative to pH = 8, indicating that the particles become larger. At pH = 4, the particle size increases further, mainly distributed between 100 and 1000 microns. This shows that as the pH value decreases, the particles tend to form larger aggregates.
[0067] (3) The size of organic matter and metal flocs is shear-dependent
[0068] The particle size distribution of the Al-OM floccules in this embodiment at different disturbance speeds was tested using a Mastersizer 2000 laser particle size analyzer. The results are as follows: Figure 2 As shown. It was found that when the stirring rates were 150 rpm, 300 rpm, and 450 rpm, the grading curve shifted to the left, and the corresponding maximum particle sizes were 1956, 832, and 335 μm, respectively. The floc sizes corresponding to the maximum peaks were 708.76, 218.74, and 106.32 μm, respectively. This shows that with the increase in rotation speed, the Al-OM floc particles are broken and the particle size becomes smaller. Therefore, when the injection speed is low, the Al-OM floc particle size is larger and is easily trapped in the particle pores to block the pores. The permeability coefficient decreases faster, and the subsequent slurry is prevented from diffusing to a longer distance. When the grouting speed is faster, the Al-OM floc is smaller in size and can diffuse over a longer distance.
[0069] It can be seen that the present invention first mixes the metal ion solution with the soluble organic matter solution to generate a solution containing flocs. Subsequently, the size of the flocs is accurately controlled by the rotation speed of the mixer according to the pore size of the soil on site. When the injection speed is reduced, the flocs will increase and effectively block the pores in the soil, thereby forming a barrier, reducing the permeability coefficient of the soil, and effectively solving the leakage problem. This method not only improves the application effect of the grouting material, but also enhances its applicability in actual engineering.
[0070] Example 2: Injection test of green seepage reduction grouting material and verification of grouting effect
[0071] According to Example 1, 100% water-soluble potassium humate is used as organic matter, and AlCl3·6H2O is used as a metal source to prepare a slurry, and then a one-dimensional injection device (see Chinese invention patent CN208653993U for details) is used to perform an injection test. The sand column used in this test is Dorsilit quartz sand (Dorsilit No.9), with an average particle size range of 0.1-0.5mm, wherein the injection container is a PVC pipe with an inner diameter of 6.7cm, an outer diameter of 7cm, and a height of 160cm, and screw caps are used to lock the two ends of the column to ensure that there is no liquid leakage during the injection process. The PVC pipe is placed vertically, and the Al-OM slurry is injected from the bottom through a Watson-marlow 120U / DV peristaltic pump and an extrusion hose with an inner diameter of 4mm, and discharged from the top. The injection rate can be controlled by adjusting the speed of the pump (1-200rmp). For example, when the speed is 120rpm, the injection rate is 1.3×10 -6 m 3 / s. Pore pressure sensors were installed at both ends to monitor the changes in pore water pressure. Before injection, the slurry was continuously stirred at a constant speed with a magnetic stirrer to ensure that the Al-OM flocs did not settle. Since the permeability coefficient of the sand continued to decrease during the injection process and the pore water pressure at the bottom continued to increase, the pump used could not ensure that the slurry was injected at a constant rate. Therefore, the injection volume of the slurry was calculated by the amount of liquid discharged, and the data was automatically recorded by MP3 software.
[0072] The calculation formula is as follows:
[0073]
[0074] Where k is the permeability coefficient (m / s), Q is the flow rate of the injected liquid (m 3 / s), A is the cross-sectional area of the cylinder (m 2 ), H is the height of the sample (m), and Δp is the difference between the pressure sensors at both ends of the PVC pipe.
[0075] Figure 3 The photo shows a one-dimensional grouting test using a one-dimensional injection device, where the black substance at the bottom of the sand column is aluminum-organic matter (Al-OM) flocs trapped in the pores. It can be observed that as the injection process progresses, the Al-OM flocs in the slurry are gradually trapped in the sand sample, accumulate at the bottom of the sand column, and diffuse upward. After injecting 3 times the pore volume in the sand column, the filling height of Al-OM in the sand column reaches 17 cm.
[0076] By comparing the resistivity data after injection, the effectiveness of the injection effect can be evaluated. Through the visualized resistivity distribution diagram, the diffusion and distribution of metal-organic flocs in the soil can be intuitively analyzed to further verify its injection effect. The resistivity distribution of the sand column is measured by resistivity imaging. The specific steps are as follows: After the test, the position of the pore pressure sensor is set along the side wall of the sand column, the electrode is buried, and a constant current is applied to the electrode through the data acquisition instrument. The voltage difference between the electrodes is measured and the data is recorded. The resistivity at different depths is calculated using the inversion algorithm, and the resistivity profile is drawn. Then, the resistivity distribution is analyzed to evaluate the uniformity and liquid penetration in the sand column.
[0077] In the laboratory, the resistance method is used to detect the injection effect of metal-organic flocs, which is mainly based on the relationship between electrical conductivity and soil pore structure and the properties of the injected material. When metal-organic flocs are injected into the soil, these flocs will fill the pores of the soil and change the electrical conductivity of the soil. The specific principle is as follows:
[0078] (1) Changes in conductivity: The injection of metal-organic flocs will affect the movement of water in the soil and the ion concentration of pore water, thereby changing the conductivity of the soil. By measuring the changes in conductivity, the distribution of the injected material and the filling of the pores can be indirectly reflected. (2) Resistance measurement: When using the resistance method, electrodes are usually placed in the experimental soil sample, and the resistance is calculated by applying a known voltage and measuring the current. According to Ohm's law (R = V / I), the resistance value of the sample can be obtained. With the injection of metal-organic flocs, the resistance value of the soil will decrease, indicating that the injected material has effectively filled the pores of the soil. (3) Data analysis: By comparing and analyzing the resistance values at different time points and different injection concentrations, the injection effect can be evaluated, thereby judging the distribution of metal-organic flocs and their stability in the soil. It can be seen that the resistance method provides an effective quantitative detection method for the injection effect of metal-organic flocs, reflecting the effectiveness of the injected material and the permeability characteristics of the soil through changes in conductivity.
[0079] Figure 4 The following are photos of the distribution of slurry in the soil column after the injection test and the corresponding resistivity distribution map. The actual photo on the left shows the physical distribution of the slurry after injection, and the deposition of the slurry at different heights can be intuitively seen. The resistivity maps in the middle and on the right show the distribution of resistivity inside the soil column through color changes. It can be seen that the resistivity value decreases at the location where the slurry is distributed, mainly because the presence of flocs reduces the resistance value. Therefore, the use of resistivity can analyze the diffusion and distribution of the slurry in the soil column, which helps to evaluate the effect and uniformity of slurry injection.
[0080] Furthermore, in order to test the injectability of the grout, five groups of injection tests with different initial grouting rates were carried out. The injection rates were 3.3×10 -7 m 3 ·s -1 , 5.5×10 -7 m 3 ·s -1 , 1.1×10 -6 m 3 ·s -1 , 1.6×10 - 6 m 3 ·s -1 , 2.2×10 -6 m 3 ·s -1 , the results are as follows Figure 5 As shown in the figure, with the increase of grouting volume, Al-OM flocs continue to accumulate in the sand column and block the water flow channel, and the permeability coefficient continues to decrease. Due to the different initial permeability coefficients k0, the permeability coefficients are normalized (k0 / k) for comparison. The permeability coefficient decrease rate is negatively correlated with the grouting speed and decreases with the increase of grouting speed. When the grouting volume is the same and the slurry is injected at a faster speed, the permeability coefficient decreases relatively less. When the grouting speed is 3.3×10 - 7 m 3 ·s -1 , 5.5×10 -7 m 3 ·s -1 , 1.1×10 -6 m 3 ·s -1 When the amount of injected slurry increases, the permeability coefficient can be reduced by more than 60 times, showing an excellent permeability reduction effect. Figure 2 The verification results are consistent with those in , that is, the faster the injection speed, the smaller the size of the flocs. Figure 6 The distribution length of Al-OM floccules in the sand column after the same slurry is injected using an injection device is shown. It can be seen that as the injection rate increases, the injection length increases. Therefore, the injectability of the injected aluminum-organic floccules can be adjusted by controlling the shear rate. The above results demonstrate the potential of the grouting material of the present invention as an effective permeability reducer in geotechnical engineering.
[0081] Based on Examples 1 and 2, the present invention has developed a green grouting material with controllable size. The material generates flocculent precipitates through chemical reactions between organic matter and metal ions, with sizes ranging from 17 μm to 1000 μm. The size of the floccules can be precisely controlled by adjusting the reaction conditions (such as stirring rate or pH value) as required. For example, the stirring rate affects the size of the metal-organic floccules, such as Figure 2 As shown in Figure 2, the size of Al-OM flocs decreases with increasing stirring speed. Figure 1 As shown in the figure, at the same stirring rate (300 rpm), the size of the flocs increases with the decrease of pH value. This feature enables the slurry to be used in geotechnical engineering to inject the generated flocs into the pores of the soil through infiltration grouting, thereby achieving effective pore plugging and permeability control (the principle is as follows Figure 7 Therefore, the method of the present invention not only imitates the ashing process in nature, but also provides flexible size control capability, and is suitable for precise infiltration reduction treatment under different engineering requirements.
[0082] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A seepage reduction grouting material, characterized in that: The seepage reduction grouting material comprises metal ions and soluble organic matter.
2. A seepage reduction grouting material according to claim 1, characterized in that: The metal ions include Al 3+ or Fe 3+ , provided by the corresponding metal salts.
3. A seepage reduction grouting material according to claim 1, characterized in that: The soluble organic matter includes water-soluble potassium humate or water-soluble sodium humate.
4. A seepage reduction grouting construction process, characterized in that: The seepage-reducing grouting material described in any one of claims 1 to 3 is used as the grouting raw material, metal ions and soluble organic matter are dissolved in degassed and demineralized water respectively, the two solutions are mixed to generate metal-organic flocs, and then the flocs are injected into the pores of the soil by infiltration grouting, thereby achieving effective pore plugging and permeability control.
5. A seepage reduction grouting construction process according to claim 4, characterized in that: The grouting speed is 1.1×10 - 6 m 3 ·s -1 -5.5×10 -7 m 3 ·s -1 .
6. A seepage reduction grouting construction process according to claim 4, characterized in that: After mixing the two solutions, the pH of the mixed solution is 4-8.
7. A seepage reduction grouting construction process according to claim 4, characterized in that: After the metal-organic flocs are generated, the size of the flocs is 17 μm-1000 μm.
8. A seepage reduction grouting construction process according to claim 4, characterized in that: The molar mass ratio of metal ions to soluble organic matter is greater than 0.
06.
9. A seepage reduction grouting construction process according to claim 4, characterized in that: During the grouting process, the electrical resistance method is used to detect the injection effect of metal-organic flocs.
Citation Information
Patent Citations
Indoor test device of impervious material infiltration slip casting
CN208653993U